Serum concentration of adhesion molecules in patients with delayed ischaemic neurological deficit after aneurysmal subarachnoid haemorrhage: the immunoglobulin and selectin superfamilies. Issue 3 (1st September 2001) - Nissen, J J; Mantle, D; Gregson, B; Mendelow, A D
Abstract : OBJECTIVES: Adhesion molecules are involved in the pathogenesis of cerebral ischaemia and may play a part in the pathophysiology of delayed ischaemic neurological deficit (DIND) after aneurysmal subarachnoid haemorrhage. It was hypothesised that after aneurysmal subarachnoid haemorrhage, adhesion molecules may play a part in the pathophysiology of DIND as reflected by significantly altered serum concentrations in patients with and without DIND. METHODS: In a prospective study, mean serum concentrations of ICAM-1, VCAM-1, PECAM, and E, P, and L-selectin were compared between patients without (n=23) and with (n=13) DIND in patients with World Federation of Neurological Surgeons (WFNS) grades 1 or 2 subarachnoid haemorrhage. Serum was sampled from patients within 2 days of haemorrhage and on alternate days until discharge. Concentrations of adhesion molecules were measured by standard procedures using commercially available enzyme linked immunoabsorbent assays. RESULTS: There were non-significant differences in serum concentrations of ICAM-1 (290.8 ng/ml v 238.4 ng/ml, p=0.0525), VCAM-1 (553.2 ng/ml v 425.8 ng/ml, p=0.053), and PECAM (22.0 ng/ml v 21.0 ng/ml, p=0.56) between patients without and with DIND respectively. The E-selectin concentration between the two patient groups (44.0 ng/ml v 37.4 ng/ml, p=0.33) was similar. The P-selectin concentration, however, was significantly higher in patients with DIND compared with those patients without DIND (149.5 ng/ml v 112.9 ng/ml, p=0.039). By contrast, serum L-selectin concentrations were significantly lower in patients with DIND (633.8 ng/ml v 897.9 ng/ml, p=0.013). CONCLUSIONS: Of all the adhesion molecules examined in this study, P and L-selectin are involved in the pathophysiology of DIND after aneurysmal subarachnoid haemorrhage.